2016
DOI: 10.1097/igc.0000000000000719
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Appendicectomies at Surgery for Mucinous Ovarian Neoplasms: Report From A UK Center and Review of Literature

Abstract: In MOT, an abnormal appearing appendix should be excised. If the appendix is grossly normal, our data do not support performing an appendicectomy as part of a surgical staging procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The authors concluded that normal-looking appendix could be left in situ in case of ovarian mucinous adenocarcinoma. 10 Although routine appendectomy could be related to postoperative complication, 2 studies did not find an increased number of complications after 40 and 155 cases of appendectomy, respectively. 8,9 In additional 121 cases of routine prophylactic appendectomy during laparoscopic hysterectomy for benign conditions, Wang et al 11 did not experience an increase in postoperative complications.…”
Section: Figurementioning
confidence: 98%
“…The authors concluded that normal-looking appendix could be left in situ in case of ovarian mucinous adenocarcinoma. 10 Although routine appendectomy could be related to postoperative complication, 2 studies did not find an increased number of complications after 40 and 155 cases of appendectomy, respectively. 8,9 In additional 121 cases of routine prophylactic appendectomy during laparoscopic hysterectomy for benign conditions, Wang et al 11 did not experience an increase in postoperative complications.…”
Section: Figurementioning
confidence: 98%
“…However, if the appendix is grossly normal, which is the case for this patient, performing an appendicectomy as part of the surgical staging procedure seems not to be necessary. [30] Whether or not our surgical procedure is a better option will be eventually determined by the patient's survival period.…”
Section: Discussionmentioning
confidence: 99%
“…While appendicectomy is commonly performed in the staging of MBOT, data from several studies do not support this practice in the presence of a macroscopically normal appendix. 23,24 Intraoperative frozen section, not utilized in this cohort as this service was not routinely available throughout this …”
Section: Discussionmentioning
confidence: 99%